Relationship between instructor's entrepreneurship pedagogical content knowledge on student's entrepreneurial intention at Kuala Langat Community College - Sipon, Merhayati; Lope Pihie, Zaidatol Akmaliah; Abd Rahman, Fadzilah; Abdul Manaf, Umi Kalthom (Jabatan Pendidikan Politeknik, 2018)
A preliminary studies to investigate the nature of pedagogical content knowledge developed in an entrepreneurship subject/ course and its association with entrepreneurial intention in a group of students, who were enrolled in Modul Asas Kemahiran Keusahawanan‘s subject at Kuala Langat Community College. Simple random sampling were implemented in distributing the questionnaire and a 187 respondent has returned the complete questionnaire. A simple curriculum overview of Modul Asas Keusahawanan was done and the collected data were analysed using descriptive and multiple stepwise linear regression in SPSS. The findings showed that there is no significant relationship between EPCK (β = .006, p = .962 and is >.05) towards entrepreneurial intention. However, the regression test in assessing the relationship between each subcontract demonstrates that a combination of knowledge of concepts representations and knowledge of learners represents 70.6% variance in the relationship between entrepreneurial PCK and entrepreneurial intentions. This study provides more emphasis on the needs of teachers to master the knowledge of student representation and knowledge, in delivering and teaching the Modul kemahiran Asas Keusahawanan to students. In addition, students believe that their instructors' knowledge in entrepreneurial pedagogy is sufficient.